Adolescent Executive Function Measurements in Indonesia : Systematic Review and Implications in Educational Settings - Ardra, Owena; Hendrawan, Donny (LPPM Universitas Pendidikan Mandalika, 2024)
This study examines the landscape of executive function (EF) assessments for Indonesian adolescents, focusing on their psychometric properties. The adolescent development phase, marked by cognitive growth, presents opportunities and risks, especially in education settings where well-developed EF is beneficial. This research used a qualitative approach, with a systematic literature review method using the PRISMA (Preferred Reporting Items for Systematic Review and Meta-analysis), analyzing peer-reviewed empirical studies from databases such as SCOPUS and others, focusing on EF measurements for adolescents in Indonesia from 2014 to 2024. Nine studies met the inclusion criteria, highlighting tools like the Behavior Rating Inventory of Executive Function (BRIEF)-Indonesian version, Executive Skills Questionnaire-Revised (ESQ-R), Executive Function Questionnaire (EFQ), and performance-based measures like the Wisconsin Card Sorting Test and Stroop Test. Using content analysis, this study reveals that while the BRIEF is widely used in clinical studies, its applicability in educational settings requires improvement. The findings highlight the importance of adapting EF tools with cultural sensitivity and developing new comprehensive assessments with clear psychometric properties regarding all critical EF components. In recommendations, the study pinpoints a multi-method approach combining inventory-based and performance-based measures to provide a thorough understanding of EF while maintaining practicality for educational settings. The implications for advancing EF research and practice in Indonesia, particularly in education, are discussed, emphasizing the need for reliable, valid, culturally sensitive, and accessible assessment tools.